Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Kemampuan Berpikir Kreatif Matematis Siswa SMP - Febri Muhamar Chaniago; Riri Syafitri Lubis; Suci Dahlya Narpila (Educational Journal, 2026)
The research, entitled "The Effect of the Think Pair Share Cooperative Learning Model on Junior High School Students' Mathematical Creative Thinking Skills," is based on the fact that in mathematics learning, teachers often teach students in conventional learning, where learning always focuses on teacher explanations. Consequently, not many teachers are able to help students develop thinking skills in solving mathematical problems. Therefore, teachers need to use good learning methods to help test students' creative thinking skills in mathematics. The research methodology used quantitative research with a posttest control group design approach. The study population was students of Madrasah Tsanawiyah Al Ittihadiyah Medan with a sample size of 22 students in the experimental group and 22 in the control group. The sampling technique used by the researcher was cluster random sampling. The data collection technique was a mathematical creative thinking ability test. Instrument validity testing used each formula assisted by using Microsoft Excel. An Independent Sample t-Test was also used to test the research hypothesis. The results of the study revealed that there was an influence between the cooperative learning model of the think pair share type on the mathematical creative thinking abilities of junior high school students. This can be seen from the results of the Independent sample t-test which showed that the significance value was 0.000 < 0.05 so that H0 was rejected and H1 was accepted. From the research findings above, the think pair share type cooperative learning model can be used as an alternative learning model in the mathematics learning process, especially for material that requires creative thinking skills.